A critique of Augusto Baol’s ‘ Theater of the Oppressed within the context of Post Independent Zimbabwe - Rwafa, Urther (Unisa Press, 2016)
During the 1970s, Augusto Baol, a Brazilian scholar laid out theoretical and practical foundation to what he called: Theatre of the oppressed’ (1979). Rejecting the Aristotelian poetics of despair and bourgeois ‘illusionism’, Baol evolved and experimented with interrogative theatre that focused on performer-spectator solidarity. This article explores some tenets of the genre of the theatre of the oppressed to tease out philosophical and ideological arguments that underpin the conception and development of theatre practiced by the oppressed in Zimbabwe. It is argued that while the dominant classes in Zimbabwe may wish to narrow and univocalize meaning through their censorship of cultural works of art, symbolic instabilities within the language of theatre has the capacity to subvert preferred readings that work to prevent realisation of alternative histories and memories. The article will exemplify the nature and manifestations of state restrictions on theatre of the oppressed by making special reference to the dialectics of the play ‘Workshop Negative’ written and produced by Cont Mhlanga in 1987.